An annotated checklist of scale insects (Hemiptera: Coccoidea) of Saint Lucia, Lesser Antilles - Malumphy, Chris (Zootaxa, 2014)
An annotated list of 83 scale insect species (Hemiptera: Sterorrhyncha: Coccoidea) recorded from Saint Lucia is presented, based on data gathered from UK quarantine interceptions, samples collected in an urban coastal habitat in the North West of the Island in 2013, and published records. Thirty-three species (40%) are recorded for the first time for the country, including Dysmicoccus joannesiae (Costa Lima), a South American mealybug, and Poliaspoides formosana (Takahashi), an Asian armoured scale insect pest of bamboo, which are new for the Caribbean region. The economic, environmental and social impacts caused by introduced exotic species of scale insect are discussed. Two predatory midges Diadiplosis ?coccidivora (Felt) and Diadiplosis multifila (Felt) (Diptera: Cecidomyiidae) are recorded for the first time from Saint Lucia. The latter species was observed causing 90% mortality of a large infestation of passion vine mealybug Planococcus minor (Maskell) on soursop fruit.